AGING COEFFICIENT IN DIFFERENT RELIGIOUS GROUPS IN IRAN - D.D. Farhud; H. Sadighi; H. Pour-Jafari; A.M. Sheibni (Tehran University of Medical Sciences, 1998)
Aging Coefficient (AC), or aged-child ratio, is the number of individuals aged 65 years and over, divided by the number of individuals aged 0-14, multiplied by 100. In this point-descriptive study, the aging coefficient has been calculated for the followers of four different religions, for the past four respective decades, according to sex and locality. Overall age composition in different religious groups, in a decreasing order is: Christians, Jews, and Zoroastrians showed a slight decrease in the 80's and a higher increase afterward. Moslems show a more consistent mode, but with a slight increase in the last decade; but in all cases AC has been lower than 15, presenting a higher proportion of a young population or lower aged group. The increase of AC in each group can be caused by the old age survival, i.e. increasing life expectancy, or decreasing birth rate